Resposisi Agama dalam Perang: Peran Nahdlatul Ulama dalam Usaha Mendukung Transformasi Konflik Afghanistan 2013-2019 - Ayu Rikza (Journal of Integrative International Relations, 2021)
Religion is two blades which one side can be a tool to legitimize stabbing humans, but on the other hand can be a source of hope. Religion in the Afghanistan conflict is not only a justification for jihadist acts, but also a hidden cause of conflict between religious communities there which gave birth to ethnic and religious group disintegration. This is compounded by the absence of structural institutions that accommodate national unity. The difficulty of reconciliation carried out by state actors and international organizations in the resolution of the Afghanistan conflict has led to the use of second-track diplomacy to help resolve this never-ending revolution. The appointment of Nahdlatul Ulama (NU) which is a religious-based civil society organization as a mediator by Indonesia in supporting reconciliation efforts is the turning point of the conflict transformation effort in Afghanistan. NU has a vision to create positive peace that aims to mitigate religious teachings in contributing to the conflict and eliminate the justification of religion as a tool to perpetuate civil conflict. In the context of public diplomacy, NU uses a model of religious diplomacy that can be defined as "the use of religion to communicate with the global public as a way to overcome the Afghan conflict”. This paper seeks to explain how NU uses religious diplomacy in conflict transformation efforts in Afghanistan.